A new, palliative care led, pathway approach to care in metastatic cancer of unknown primary origin. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Hughes, Philippa; Farrington, Clare; Brooks, David; Bath, Peter; Noble, Bill
Abstract : Background: Recent NICE guidance highlights inequity of care for CUP compared to site-specific cancer, and recommends instigating CUP teams, to include a palliative care physician, oncologist and specialist nurse. Aim and methods: Within a study to evaluate the development of a CUP team and pathway, we undertook a retrospective cross-sectional analysis of patient data before and during implementation. Results: Eighty-eight patients were identified with CUP during two six-month periods: median age 75 years. Fifty-two patients (59.1%) scored 3–4 on ECOG Performance Scale (PS). Thirty-nine (44.3%) were referred for consideration of Tumour Directed Treatment (TDT) and twenty-three (26.1%) completed the planned treatment. Median time from presentation to death was 40 days. Of 88 patients, 50 were pre pathway-implementation; 38 postimplementation, not differing significantly in gender, age or PS. In the postimplementation group, patients had experienced varying degrees of application of the new pathway approach. Time from referral to instigation of definitive treatment ranged from 0 to 115 days in the prepathway group, and from 0 to 74 days in the postimplementation group. No significant difference was found between the groups in the mean rank of these times: prepathway 40.05 days; postimplementation 33.77 days (Z=−1.2348; p=0.217). Fourteen (28%) prepathway patients and 9 (23.7%) postimplementation patients received TDT as planned or with modifications. Prepathway; of 48 deaths, 7 were at home, 30 in hospital, 10 in a hospice, (one place unknown): postimplementation; of 33 deaths, 12 were at home, 14 in hospital and 7 in a hospice. Discussion and conclusion: The majority of patients presenting with CUP have poor performance status and short life expectancy. A minority received tumour directed treatment. Early palliative care involvement has the potential to aid symptom management and curtail the longest investigatory periods, without reducing oncology referral. Further evaluation is warranted when the pathway is embedded.